Digitalisation and AI are conducive to increasing the attractiveness of vocational education and training - Esser, Friedrich Hubert [Verfasser] (My University, 2019)
"Digitalisation and artificial intelligence continue to be decisive topics within politics, trade and industry, and society. BIBB has acted in a timely manner to address the associated question as to what consequences will ensue for the world of work and employment. Extensive research and development findings now provide a basis for delivering responses." (Author's abstract ; BIBB-Doku)
Digitalisierung und KI sind Steilvorlagen für mehr Attraktivität in der Berufsbildung